SERPINA5 inhibits tumor cell migration by modulating the fibronectin‐integrin β1 signaling pathway in hepatocellular carcinoma. Issue 2 (18th December 2013) - Jing, Ying; Jia, Deshui; Wong, Chun-Ming; Oi-Lin Ng, Irene; Zhang, Zhenfeng; Liu, Li; Wang, Qifeng; Zhao, Fangyu; Li, Jinjun; Yao, Ming; Wu, Xingzhong; He, Xianghuo
Abstract : In our previous study, we identified 1241 loci with somatic copy number alterations in human hepatocellular carcinoma (HCC) using Affymetrix SNP 6.0 arrays, and a putative cancer gene SERPINA5 was uncovered in a novel chromosomal region with recurrent copy number loss at 14q31.1–32.13. The SERPINA5 was reported to be deregulated in renal, breast, prostate and ovarian cancers. However, the roles of SERPINA5 in cancer remain greatly elusive. In this study, we found that the DNA dosage and expression level of the SERPINA5 gene were significantly decreased in HCC by quantitative real‐time PCR. Notably, the expression levels of SERPINA5 negatively correlated with malignant progression of HCC. The SERPINA5 gene was further observed to reduce in vitro and in vivo metastatic potential of HCC cells. Moreover, secreted SERPINA5 protein also could inhibit the metastatic ability of HCC cells. Finally, we discovered that one of the mechanisms explaining SERPINA5 inhibition of HCC metastasis is through direct interaction with fibronectin and disruption of the fibronectin–integrin signaling pathway. These findings highlight an important role of SERPINA5 in the regulation of migratory and metastatic potentials of HCC and suggest a potential application of SERPINA5 in cancer treatment. Highlights: Downregulation of SERPINA5 negatively correlates with malignant progression of HCC. SERPINA5 reduces in vitro and in vivo metastatic potential of HCC cells. SERPINA5 inhibits HCC cell migration by directly interacting with fibronectin. SERPINA5 disrupts the fibronectin–integrin β1 signaling pathway.